2023
DOI: 10.1002/anie.202300998
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Biosynthesis of Cihunamides, Macrocyclic Antibacterial RiPPs with a Unique C−N Linkage Formed by CYP450 Catalysis

Abstract: Cihunamides A–D (1–4), novel antibacterial RiPPs, were isolated from volcanic‐island‐derived Streptomyces sp. The structures of 1–4 were elucidated by 1H, 13C, and 15N NMR, MS, and chemical derivatization; they contain a tetrapeptide core composed of WNIW, cyclized by a unique C−N linkage between two Trp units. Genome mining of the producer strain revealed two biosynthetic genes encoding a cytochrome P450 enzyme and a precursor peptide. Heterologous co‐expression of the core genes demonstrated the biosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 31 publications
1
32
1
Order By: Relevance
“…The reported compound in this class is a structurally complex molecule also called atropitides or bitryptides. ,,, The precursor peptide of this class contains a conserved KSLK motif in the N -terminal leader peptide region, while the core peptide region contains a conserved WYxWY motif. The presence of multiple conserved aromatic amino acids in the core peptide suggests that these corresponding peptides may also possess complex planar and topological structures.…”
Section: Resultsmentioning
confidence: 99%
“…The reported compound in this class is a structurally complex molecule also called atropitides or bitryptides. ,,, The precursor peptide of this class contains a conserved KSLK motif in the N -terminal leader peptide region, while the core peptide region contains a conserved WYxWY motif. The presence of multiple conserved aromatic amino acids in the core peptide suggests that these corresponding peptides may also possess complex planar and topological structures.…”
Section: Resultsmentioning
confidence: 99%
“…Coexpression of cihA and cihB in Escherichia coli suggests that the CihB enzyme is sufficient for the core macrocyclization of CihA in the absence of additional redox partners. 59 Another survey of 21,911 actinobacteria genomes generated 1957 potential BGCs in total, which are composed of a P450 gene and a precursor peptide gene with at least two aromatic residues (Trp, Tyr, or His) encoded in the C-terminus. The BGCs (scn and mci) from Streptomyces sp.…”
Section: P450s In Cittilin and Atropitide (Atropopeptide) Biosynthesesmentioning
confidence: 99%
“…During the evaluation of this Review, cihunamides A–D ( 94 – 97 ) and the peptide fragment 99 with atypical Trp-Trp linkages along with the peptide fragment 101 containing a Tyr-Trp linkage were reported. , In silico analysis of the cihunamides producing strain reveals two adjacent genes encoding a precursor peptide (CihA, 93 ) with the C-terminal sequence “TWNIWYS” and a P450 (CihB), which is very closely related to the atropitide family members in sequences. Nonetheless, cihunamides exhibit a distinct C–N linkage between two tryptophans and lack the class-defining feature of atropitides, (i.e., noncanonical atropisomerism resulted from multiple covalent linkages) (Figure D).…”
Section: P450s In Cittilin and Atropitide (Atropopeptide) Biosynthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cihunamides A 6 –D, produced by a volcanic-island-derived Streptomyces species, are peptides featuring a C–N linkage between two tryptophan units. 6 Genome mining has demonstrated that the cihunamides are ribosomally synthesised and post-translationally modified peptides (RiPPs) and that the C–N linkage is formed by a cytochrome P450 enzyme. Crossiellidines A 7 –F are unprecedented pyrazine-alkylguanidine metabolites from Crossiella sp.…”
mentioning
confidence: 99%